1997
DOI: 10.1523/jneurosci.17-18-07079.1997
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Analyses of Human Cerebral Cortex Using a Surface-Based Atlas

Abstract: We have analyzed the geometry, geography, and functional organization of human cerebral cortex using surface reconstructions and cortical flat maps of the left and right hemispheres generated from a digital atlas (the Visible Man). The total surface area of the reconstructed Visible Man neocortex is 1570 cm 2 (both hemispheres), ϳ70% of which is buried in sulci. By linking the Visible Man cerebrum to the Talairach stereotaxic coordinate space, the locations of activation foci reported in neuroimaging studies c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
299
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 424 publications
(315 citation statements)
references
References 68 publications
15
299
0
1
Order By: Relevance
“…Surface-based analysis, display, and 2-D coordinate systems have been proposed (Drury et al, 1996;Fischl et al, 1999a,b;Van Essen et al, 1998Van Essen and Drury, 1997). Indeed cortical surfaces are now widely used for display purposes, including this study.…”
Section: Discussionmentioning
confidence: 99%
“…Surface-based analysis, display, and 2-D coordinate systems have been proposed (Drury et al, 1996;Fischl et al, 1999a,b;Van Essen et al, 1998Van Essen and Drury, 1997). Indeed cortical surfaces are now widely used for display purposes, including this study.…”
Section: Discussionmentioning
confidence: 99%
“…They localize volume reductions to specific regions of the structure and therefore may give us additional insights into the nature of their involvement in TS and provide direction to future studies. Because neuroanatomical shapes may be influenced by patterns of neuroanatomical connections (Van Essen, 1997), metrics related to shape may be particularly sensitive to subtle disturbances in neuronal organization during development that underlie neuropsychiatric disorders such as TS.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the 3D distance between anatomical landmarks in different brains after Talairach normalization can be over 10mm (Steinmetz et al, 1990;Thompson and Toga, 1996;Van Essen and Drury, 1997). Thus, precise localization of functional areas with respect to gyral and sulcal landmarks is not possible.…”
Section: Introductionmentioning
confidence: 99%